Synthesis and Crystal Structure of 2-Methyl-3-ethyl methanoate benzo[h]quinoline - Benboudiaf, A.; Bouchoul, A.; Ouahab, L.; Bouaoud, S.E. (Asian Journal of Chemistry, 2016)
The synthesis of a new benzoquinoline derivative from an enamine using Vilsmeier reagent has been reported. The 2-methyl-3-ethyl methanoate benzo[h]quinoline obtained was identified by classic and usual spectroscopic techniques as well as X-ray structural determination.